Identifikasi Sektoral Kota Tarakan - Wijayanti, Asih Kusuma (Ekonomika, 2010)
The purpose of this study to determine the economys performance by comparing the City of Tarakan In East Kalimantan Provinces economy. Identify and analyze the sector/subsector economic potential in the City of Tarakan; then find a picture of patterns and structures of economic growth the City Tarakan; and estimate the economic potential that can be developed in the CIty of Tarakan. All observed during period 2002-2006. Analysis tool used is The Shift Share analysis and Location. Quotient (LQ). The results of the analysis Location Quotient (LQ) indicates that the City of Tarakan has seven dominant sector of the agicultural sector, electricity sector, gas and water supply, building sector, trade, hotels, and restaurants, transport, and communication sector, financial sector, real estate and business services, and the services sector. This is supported by the index value obtained from the results of Dynamic Location Quotient analysis with an average value of 1,55. Furthermore, other sectors that have not been favored as a sector Quotient Mining and Quarrying sector (1,66). From the results of the Shift Share analysis classic, as a whole during the period of analysis 2002-2006 year, GDP Tarakan City has experienced a change (increase) is quite significant, meaning an increase regional economic performance. This shows that in the Tarakan City economic development has occured the process of economic structural change. Key Words: Location Quotient, Sector Competitive, Shift Share